2008
DOI: 10.1093/hmg/ddn156
|View full text |Cite
|
Sign up to set email alerts
|

Reduced SMN protein impairs maturation of the neuromuscular junctions in mouse models of spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA) is a common pediatric neuromuscular disorder caused by insufficient levels of the survival of motor neuron (SMN) protein. Studies involving SMA patients and animal models expressing the human SMN2 gene have yielded relatively little information about the earliest cellular consequences of reduced SMN protein. In this study, we have used severe- and mild-SMN2 expressing mouse models of SMA as well as material from human patients to understand the initial stages of neurodegeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

34
412
6
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 392 publications
(453 citation statements)
references
References 51 publications
34
412
6
1
Order By: Relevance
“…Recent studies revealed NMJ defects as a characteristic feature of SMA pathology and potentially the cause of, or a contributor to, motor neuron death and muscle atrophy (Kariya et al 2008). Muscles are selectively affected, and one of the most vulnerable muscles in the SMND7 mouse model is the longissimus capitus, which shows ;28% fully denervated fibers in this slightly milder model at the end stage (P12-P14) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies revealed NMJ defects as a characteristic feature of SMA pathology and potentially the cause of, or a contributor to, motor neuron death and muscle atrophy (Kariya et al 2008). Muscles are selectively affected, and one of the most vulnerable muscles in the SMND7 mouse model is the longissimus capitus, which shows ;28% fully denervated fibers in this slightly milder model at the end stage (P12-P14) ).…”
Section: Resultsmentioning
confidence: 99%
“…However, how suboptimal levels of SMN lead to SMA is largely unknown. Multiple studies in SMA mouse models revealed widespread synaptic defects in neuromuscular junctions (NMJs), including neurofilament accumulation, poor terminal arborization, immature endplates, reduced quantal content, disturbed calcium homeostasis, and decreased remodeling potential; these defects precede motor neuron death (Cifuentes-Diaz et al 2002;Le et al 2005;Jablonka et al 2007;Kariya et al 2008;Murray et al 2008Murray et al , 2012Kong et al 2009;Ling et al 2010;Ruiz et al 2010;Lee et al 2011), suggesting that the NMJ alterations are the initial consequence of SMN deficiency, Ó 2015 Hua et al This article is distributed exclusively by Cold Spring Harbor Laboratory Press for the first six months after the full-issue publication date (see http://genesdev.cshlp.org/site/misc/terms.xhtml). After six months, it is available under a Creative Commons License (Attribution-NonCommercial 4.0 International), as described at http:// creativecommons.org/licenses/by-nc/4.0/.…”
mentioning
confidence: 99%
“…Importantly, no consensus has been reached regarding the cellular and molecular pathways whose perturbation results in SMA pathology. Identifying the cellular pathways most sensitive to decreased SMN is essential to understand how SMN depletion causes neuronal dysfunction/death in SMA and to accelerate therapy development.One of the early events in SMA pathogenesis is the loss of neuromuscular junction (NMJ) function, evidenced by muscle denervation, neurofilament accumulation, and delayed neuromuscular maturation (25)(26)(27). In addition, reduced neurotransmitter release and decreased numbers of docked vesicles that precede axonal degeneration and/or motor neuron death have been reported at synapses of severe SMA mouse models (28,29).…”
mentioning
confidence: 99%
“…One of the early events in SMA pathogenesis is the loss of neuromuscular junction (NMJ) function, evidenced by muscle denervation, neurofilament accumulation, and delayed neuromuscular maturation (25)(26)(27). In addition, reduced neurotransmitter release and decreased numbers of docked vesicles that precede axonal degeneration and/or motor neuron death have been reported at synapses of severe SMA mouse models (28,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation